2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7318251
|View full text |Cite
|
Sign up to set email alerts
|

Hand-eye calibration of a robot - UltraSound probe system without any 3D localizers

Abstract: Abstract-3D UltraSound (US) probes are used in clinical applications for their ease of use and ability to obtain intraoperative volumes. In surgical navigation applications a calibration step is needed to localize the probe in a general coordinate system. This paper presents a new hand-eye calibration method using directly the kinematic model of a robot and US volume registration data that does not require any 3D localizers. First results show a targeting error of 2.34 mm on an experimental setup using manual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Our system indicated that the error distribution of the x -axis was relatively large, which might be the unstable positioning caused by the US beamwidth in the US calibration. Our results showed that the accuracy of US positioning can still be maintained at the same level compared to other studies [ 8 , 18 , 19 ].…”
Section: Resultssupporting
confidence: 67%
“…Our system indicated that the error distribution of the x -axis was relatively large, which might be the unstable positioning caused by the US beamwidth in the US calibration. Our results showed that the accuracy of US positioning can still be maintained at the same level compared to other studies [ 8 , 18 , 19 ].…”
Section: Resultssupporting
confidence: 67%
“…In another work, 3D markers were used by Bergmeir et al [24] to realize ultrasound probe calibration with a robotic arm. In terms of none marker research work, Sarrazin et al [25] used ultrasound volume registration data to achieve calibration that does not require 3D localizers. Pachtrachai et al [26] proposed a calibration method where an instrument with known geometry is used instead of an additional calibrator.…”
Section: Related Workmentioning
confidence: 99%